The Existence of Warm Glow, Altruistic, and Egoistic Motives in Food Consumers with Ethical Claims: A Case Study of Organic Products in Indonesia - Cahyasita, Dhika (Jurusan Akuntansi Politeknik Negeri Bandung, 2025)
Abstract: This study investigates the motives behind organic food consumption and examines the relationship between warm glow and altruism. Data were collected from 219 respondents through a Likert-scale questionnaire and analyzed descriptively. The findings reveal that altruistic motives consistently outweigh egoistic motives among consumers, regardless of whether the products were purchased online or offline. Additionally, the warm glow effect demonstrates a positive correlation with altruism, providing added emotional benefits to pro-environmental and pro-social behaviors. These results suggest that incorporating emotional experiences into organic product marketing strategies can enhance consumer engagement and drive sustainable consumption.